2020
DOI: 10.1016/s2215-0366(20)30290-x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol for the treatment of cannabis use disorder: a phase 2a, double-blind, placebo-controlled, randomised, adaptive Bayesian trial

Abstract: Background: There is a substantial and unmet clinical need for pharmacological treatment of cannabis use disorders. Cannabidiol (CBD) could offer a novel treatment but it is unclear which doses might be effective or safe.Methods: Participants meeting DSM-5 cannabis use disorder criteria were allocated to four-week treatment with oral CBD at 200mg, 400mg, 800mg or placebo during a cessation attempt using a double-blinded block randomisation sequence. All received a brief psychological intervention of motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
146
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 37 publications
1
146
1
4
Order By: Relevance
“…CBD has been assessed in randomized controlled clinical trials in rare childhood epilepsies, 20,6668 schizophrenia, 18,69 type II diabetes, 70 fatty liver disease, 71 Crohn’s disease, 72 Parkinson’s disease, 73 Huntington’s disease, 74 and cannabis dependence. 19 The results from the trials in childhood epilepsy have led to its licensing as a treatment for Lennox–Gastaut syndrome and Dravet syndrome. The only other licensed medicine that contains CBD is the oromucosal spray nabiximols (Sativex), which contains similar quantities of Δ 9 -THC and CBD, and is approved as a treatment for spasticity in multiple sclerosis.…”
Section: Clinical Effects Of Cbd At Otc Dosesmentioning
confidence: 99%
See 1 more Smart Citation
“…CBD has been assessed in randomized controlled clinical trials in rare childhood epilepsies, 20,6668 schizophrenia, 18,69 type II diabetes, 70 fatty liver disease, 71 Crohn’s disease, 72 Parkinson’s disease, 73 Huntington’s disease, 74 and cannabis dependence. 19 The results from the trials in childhood epilepsy have led to its licensing as a treatment for Lennox–Gastaut syndrome and Dravet syndrome. The only other licensed medicine that contains CBD is the oromucosal spray nabiximols (Sativex), which contains similar quantities of Δ 9 -THC and CBD, and is approved as a treatment for spasticity in multiple sclerosis.…”
Section: Clinical Effects Of Cbd At Otc Dosesmentioning
confidence: 99%
“…9,10 Neuroimaging studies have shown that it has effects on brain activity, 11,12 and can modulate both the endocannabinoid and other neurotransmitter function in both volunteers and patients. 1315 Moreover, data from experimental medicine studies and clinical trials suggest that pharmaceutical grade CBD can reduce anxiety 16,17 and psychotic symptoms, 18 and has beneficial effects in addiction 19 and childhood epilepsy. 20 Endocannabinoid signalling also has a role in regulating the immune system, and CBD also has potential as an anti-inflammatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, long-term daily administration of CBD, as delivered in clinical trials (Freeman et al, 2020; Leweke et al, 2012; McGuire et al, 2018), could produce different effects on the neural correlates of reward anticipation and feedback. We only delivered a single oral 600 mg dose in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, behavioural evidence from human studies suggests that CBD can reduce the salience of drug-related cues in those with cannabis (Morgan et al, 2010) and nicotine (Hindocha et al, 2018) dependencies, and reduce drug cue-induced cravings in those addicted to heroin (Hurd et al, 2019). Additionally, a four-week treatment of CBD dose-dependently decreased cannabis use in a clinical trial of people with cannabis use disorder (Freeman et al, 2020). In all of these studies, CBD attenuated atypical reward-related behaviours conferred by addiction, suggesting a restorative effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation